Remote-sensing reflectance and true colour produced by a coupled hydrodynamic, optical, sediment, biogeochemical model of the Great Barrier Reef, Australia: Comparison with satellite data. (April 2016) - Baird, Mark E.; Cherukuru, Nagur; Jones, Emlyn; Margvelashvili, Nugzar; Mongin, Mathieu; Oubelkheir, Kadija; Ralph, Peter J.; Rizwi, Farhan; Robson, Barbara J.; Schroeder, Thomas; Skerratt, Jennifer; Steven, Andrew D.L.; et al.
Abstract: Aquatic biogeochemical models are vital tools in understanding and predicting human impacts on water clarity. In this paper, we develop a spectrally-resolved optical model that produces remote-sensing reflectance as a function of depth-resolved biogeochemical model properties such as phytoplankton biomass, suspended sediment concentrations and benthic reflectance. We compare simulated remote-sensing reflectance from a 4 km resolution coupled hydrodynamic, optical, sediment and biogeochemical model configured for the Great Barrier Reef with observed remote-sensing reflectance from the MODIS sensor at the 8 ocean colour bands. The optical model is sufficiently accurate to capture the remote-sensing reflectance that would arise from a specific biogeochemical state. Thus the mismatch between simulated and observed remote-sensing reflectance provides an excellent metric for model assessment of the coupled biogeochemical model. Finally, we combine simulated remote-sensing reflectance in a red/green/blue colour model to produce simulated true colour images during the passage of Tropical Cyclone Yasi in February 2011. Highlights: We calculate remote-sensing reflectance from a biogeochemical model state. Remote-sensing reflectance from the model is compared with observed values. Combined simulated red, green and blue reflectances make simulated true colour. Simulated reflectances and true colour are compared to observations. Simulated true colour of the Great Barrier Reef powerfully displays model output.